PRESCRIPTIVENESS AND OBLIGATION OF THE TYPOGRAPHIC STANDARD - Pořízková, Lenka (Bohemica Olomucensia, 2021)
The article deals with the development of the Czech typographic usage and its reflection in professional manuals and industry standards. In particular, it focuses on the formulation of typographic rules with regard to their obligation to the user, monitors the ratio of descriptiveness or prescriptiveness and the impact of Anglophone typography on Czech typography. It also focuses clashes of linguistically (semantically) and visually based arguments, which affect the resulting typographic practice. Attention is focused mainly on typographic phenomena directly related to the orthographic standard and commonly included in it.
Keywords: typography; orthography; book typesetting; norm; usage